"I kind of find that out by accident": probation staff experiences of pharmacological treatment for sexual preoccupation and hypersexuality. Issue 1 (9th January 2018) - Elliott, Helen; Winder, Belinda; Manby, Ellie; Edwards, Helen; Lievesley, Rebecca
Abstract : Purpose: The purpose of this paper is to explore the views and experiences of probation staff working with individuals convicted of a sexual offence who have been prescribed medication to manage sexual arousal (MMSA). Design/methodology/approach: Semi-structured interviews were utilised with a sample of probation staff (offender supervisors and managers, n =12), who supervise individuals convicted of a sexual offence, either in prison, or post-release in the community. Data were analysed using thematic analysis. Findings: Two main themes emerged: barriers for probation staff and suspicious but hopeful. Theme 1 encapsulates factors that prevent probation staff from engaging with MMSA; theme 2 highlighted the samples' uncertainty and mistrust of the use of medication as a potential tool for risk management and scepticism about individuals' motivations, particularly in the community. Research limitations/implications: The main limitation of this study was the differing levels of knowledge the sample had about MMSA and their subsequent ability to discuss MMSA other than in a theoretical sense. Practical implications: Practical implications include the need for further training for probation staff, improved collaboration between departments and ongoing support for staff to support the success of the MMSA intervention. Originality/value: This study offers a novel perspective on MMSA – that of the probation staff supervising prisoners taking MMSA. This has not been explored before, and the findings and associated implications are of importance for the treatment and care of those convicted of sexual offences.